A novel 'leadless' dielectrophoresis chip with dot matrix electrodes for patterning nanowires. (22nd June 2017) - Liu, Linbo; Chen, Ke; Huang, Di; Wang, Xin; Xiang, Nan; Ni, Zhonghua
Abstract: In this paper, we present a novel 'leadless' dielectrophoresis chip with dot matrix electrodes (LDME-DEP chip) fabricated by stacking three different functional layers. Our LDME-DEP chip excels mainly in two aspects: we for the first time applied the technique of separating the lead and the electrode pattern into two different layers to patterning nanowires which achieves continuous-area manipulation of nanowires without interference from the lead; the use of dot matrix electrodes makes the manipulation more flexible. We firstly detail the fabrication and working principle of our LDME-DEP chip and propose the scheme for washing away the nanowires with unsatisfactorily positioned postures. Then, nanowire patterning applications (e.g., letter E, square and long chain) under the combination of dielectrophoretic force and hydrodynamic force are carried out and the effect of frequency of the electric signal on assembling accuracy of nanowires is discussed.